Prevalence of group B streptococcus colonization and intrapartum antibiotic prophylaxis at Marmara University Hospital - (:unkn) unknown (My University, 2001)
Objective: The aim of this study is to identify the rectovaginal GBS colonization rate in pregnant women in our hospital and to evaluate the outcome of culture positive patients who had received intrapartum antibiotic prophylaxis (IAP) according to the protocol of The American Academy of Pediatrics. Methods: One hundred pregnant women followed at the Obstetrics outpatient clinic of Marmara University Hospital were screened at 35-37 weeks for rectovaginal group B streptococcus (GBS) colonization. The patients with risk factors or positive cultures were treated with parenteral ampicillin during the intrapartum period and the newborn of mothers who had received antibiotic prophylaxis were followed. Results: Ten patients (10%) had rectovaginal colonization whereas 1 patient had urinary tract infection secondary to GBS. All but 2 patients with GBS colonization received intrapartum antibiotic prophylaxis; one of the GBS colonized patients had immediate cesarean section delivery for fetal distress and could not receive intrapartum antibiotic prophylaxis, the culture result of the other patient was not known during labor so she could not receive intrapartum antibiotic prophylaxis. The newborn of the GBS (+) patient who had immediate C/S, developed early onset sepsis, GBS antigen was detected in his urine and this newborn was treated with intravenous antibiotics, inotropic agents and needed ventilatory support. The second infant with GBS colonized but not appropriately treated mother did not have any problems. The newborn of the GBS (+) patients whose mothers had received intrapartum antibiotic prophylaxis were discharged without any complications. Conclusion: The rectovaginal GBS colonization rate in pregnant women is 10% in our hospital, which cannot be despised. Larger multicenter screening programs are needed to assess the prevalence of GBS colonization and the efficacy of intrapartum antibiotic prophylaxis in our country.
Keywords: Antibiotic prophylaxis; Group B streptococcus infections; Pregnancy